Adhesion of Staphylococcus aureus to Candida albicans During Co-Infection Promotes Bacterial Dissemination Through the Host Immune Response - Van Dyck, Katrien; Viela, Felipe; Mathelié-Guinlet, Marion; Demuyser, Liesbeth; Hauben, Esther; Jabra-Rizk, Mary Ann; Vande Velde, Greetje; Dufrêne, Yves F.; Krom, Bastiaan P.; Van Dijck, Patrick (Frontiers in Cellular and Infection Microbiology, 2021)
Interspecies interactions greatly influence the virulence, drug tolerance and ultimately the outcome of polymicrobial biofilm infections. A synergistic interaction is observed between the fungus Candida albicans and the bacterium Staphylococcus aureus. These species are both normal commensals of most healthy humans and co-exist in several niches of the host. However, under certain circumstances, they can cause hospital-acquired infections with high morbidity and mortality rates. Using a mouse model of oral co-infection, we previously showed that an oral infection with C. albicans predisposes to a secondary systemic infection with S. aureus. Here, we unraveled this intriguing mechanism of bacterial dissemination. Using static and dynamic adhesion assays in combination with single-cell force spectroscopy, we identified C. albicans Als1 and Als3 adhesins as the molecular players involved in the interaction with S. aureus and in subsequent bacterial dissemination. Remarkably, we identified the host immune response as a key element required for bacterial dissemination. We found that the level of immunosuppression of the host plays a critical yet paradoxical role in this process. In addition, secretion of candidalysin, the C. albicans peptide responsible for immune activation and cell damage, is required for C. albicans colonization and subsequent bacterial dissemination. The physical interaction with C. albicans enhances bacterial uptake by phagocytic immune cells, thereby enabling an opportunity to disseminate.